Teh Putih sebagai Alternatif Minuman Fungsional untuk Gaya Hidup Sehat: Peluang Komersialisasi di Indonesia - Filia P. Linnarto; Kevin P. Gunawan; Milka Setiadi; Rahmad A. Ashyari; Stella Lukman (Universitas Prasetiya Mulya, 2019)
The aim of this research is to identify opportunities for white tea commercialization based on Indonesian consumer behavior and perception towards functional food. This research conducted with qualitative method by collecting data from previous researches. The result of this research shows that white tea with its high antioxidant component could be a new alternative for functional beverage for Indonesian consumer, especially its protection from degenerative diseases. White tea potential for commercialization is by the increase of health awareness, consumer concern for product benefits, economic and education level growth, and from the custom of drinking tea among Indonesian. Along with product innovation, educational promotion and effectively targets market will raise its commercial potential.